Sistema de gerenciamento digital online na gestão rural - Santos, Joana Guiel Dos (2023)
Assertive decision-making in rural areas is increasingly relevant and with thes introduction of technological advances, decisions taken directly reflect the search for growth in the agricultural sector and results. The study aims to evaluate the effectiveness of the online farm management system that allows access to information and supports rural producers in decision making. Regarding the methodological procedure, the research is characterized as a mixed research type, with qualitative and quantitative data, of an exploratory nature, and the data obtained were collected through a questionnaire via Google Forms, applied to rural producers. The main results highlight the influence of producers and their families in decision-making, with less developed activity planning using system information. Furthermore, there is frequent monitoring of data, identifying common preferences among many producers. This also points to producers' demands and needs in relation to information considered crucial and relevant.